Mixed epithelial and stromal tumor of the kidney - Shuo Zheng (Kaohsiung Journal of Medical Sciences, 2013)
A 44-year-old woman who underwent radical nephrectomy due to a left renal mass presented to our clinic. Results of the histopathological examination showed a mixed epithelial and stromal tumor of the kidney, a rare benign lesion of the kidney. The epidemiology, histopathological features, imaging features, possible pathogeneses, and treatment alternatives are discussed, and the relevant literature is reviewed. The postoperative course was uneventful, and the patient was free of local recurrence or metastasis until the last follow-up (12 months).